2015
DOI: 10.1002/jts.22026
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Mental Health Treatment‐Seeking in U.S. Active Duty Soldiers With Sexual Assault Histories

Abstract: Despite significant mental health needs among sexual assault (SA) victims in the military, little is known about treatment-seeking patterns or factors associated with service use. This study examined service use behavior, barriers, and facilitators of mental health treatment-seeking in an active duty sample of 927 U.S. Army soldiers with mental health problems. SA victims (n = 113) did not differ from non-victims on barriers or facilitators after adjusting for demographic and mental health variables, with stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…A common theme for all participants, found frequently in previous research, was reaching a crisis point prior to seeking help (Zinzow, Britt, Pury, Raymond & Burnette, 2013). One reason for reaching a crisis point seemed to be veterans’ inability to recognize their own mental health difficulties.…”
Section: Discussionmentioning
confidence: 79%
“…A common theme for all participants, found frequently in previous research, was reaching a crisis point prior to seeking help (Zinzow, Britt, Pury, Raymond & Burnette, 2013). One reason for reaching a crisis point seemed to be veterans’ inability to recognize their own mental health difficulties.…”
Section: Discussionmentioning
confidence: 79%
“…An example item had soldiers rate how often they had been bothered by “Feeling down, depressed, hopeless;” items were rated on a 4‐point scale (1 = Not at all to 4 = Nearly everyday ). The PHQ has been validated among military samples and sexual assault victims, and the reliability for the PHQ in previous studies was high (e.g., Hoge et al, ; Kroenke et al, ; α = .90, Zinzow et al, ). In the present study, Cronbach's alpha was .89.…”
Section: Methodsmentioning
confidence: 97%
“…The PCL has been demonstrated as an effective tool at assessing symptoms of PTSD in reference to criteria in correspondence to the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM‐IV‐TR; American Psychiatric Association, ). The PCL has been validated among vehicular trauma and sexual assault victims, with Cronbach's α being .94 and .95 (Blanchard, Jones‐Alexander, Buckley, & Forneris, ; Zinzow et al, ). In the present study, Cronbach's α was .95.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies showed that self-stigma and fear of societal stigma increased the likelihood of treatment dropout and decreased the likelihood of treatment utilization in military populations. 21,22 Although less well studied, clinician-held biases can compromise both a patient's willingness to accept services and the quality of clinical care that patients receive. 4,14,[23][24][25][26] Aspects of clinician behavior that can discourage patients from seeking or continuing treatment include communication styles that are negative or condescending (patronizing, dismissive) and/or emphasis on limitations and barriers (pessimism about recovery) rather than strengths and successes.…”
mentioning
confidence: 99%